Unique role of HPV16 in predicting oropharyngeal cancer risk more than other oncogenic oral HPV infections. (December 2020) - Fakhry, Carole; Fung, Nicholas; Tewari, Sakshi R.; D'Souza, Gypsyamber
Highlights: There is a wide distribution of oncogenic oral HPV types detected. HPV16 is in 20% of healthy people with oral HPV but 90% of HPV-OPSCC. HPV16 most relevant for screening as most other infections don't lead to cancer. Testing for all oncogenic types is inappropriate in oropharyngeal screening setting.